Fast Syntax in the Brain: Electrophysiological Evidence from the Rapid Parallel Visual Presentation Paradigm (RPVP). - Yun Wen; Mirault, Jonathan; Grainger, Jonathan (Journal of Experimental Psychology. Learning, Memory & Cognition, 2021)
In 2 ERP experiments participants read 4-word sequences presented for 200 ms (RPVP paradigm) and were required to decide whether the word sequences were grammatical or not. In Experiment 1, the word sequence consisted of either a grammatically correct sentence (e.g., she can sing now) or an ungrammatical scrambled sequence (e.g., sing can now she). A reduced N400 effect was obtained in the grammatically correct sequences compared to the ungrammatical sequences. In Experiment 2, the critical comparison was between 2 types of ungrammatical sequences: transposed-word sequences (e.g., you that read wrong, transposing 2 adjacent central words can form a grammatical sequence) and control sequences (e.g., you that read worry, transposing any 2 adjacent central words still forms an ungrammatical sequence). An N400 reduction was observed in the transposed-word sequences relative to the control sequences. We interpret these N400 effects as evidence that an elementary syntactic representation can be rapidly constructed on the basis of parallel processing of word identities and their parts-of-speech.